Polymeric nanocomposites with carbonaceous nanofillers for aerospace applications - Kausar, Ayesha, 1977- (Woodhead Publishing series in composites science and engineering, 2022)
Polymeric Nanocomposites with Carbonaceous Nanofillers for Aerospace Applications offers a comprehensive paperback on the aerospace relevance of polymer/carbonaceous nanofiller-based nanocomposite. This manuscript summarizes all specific information on the design, fabrication and application areas of aerospace industry that employ polymer/carbonaceous nanofiller-based nanocomposites. In addition, it points to the potential of aeronautical nanocomposites towards lightning strike, radiation shielding, anti-corrosion, electronic/optical features, thermal management, antistatic application, self-healing aptitude, and green nanocomposites. The modeling of mechanical and essential properties of aerospace nanocomposites is also discussed, along with challenges and future forecasts of polymer/carbonaceous nanofiller nanocomposites.